Obtaining biodiesel from the transesterification of soy oil - Mera Perea, Jodie Lynn; Cedeño Vera, Ivana Sophia; García Muentes, Segundo Alcides; Cevallos Cedeño, Ramón Eudoro; García Vinces, Gonzalo Oswaldo; García Ávila, Adriana Gabriela (Revista Universidad de Guayaquil, 2024)
Currently, biodiesel has become an alternative for the partial replacement of conventional diesel, due to the low cost of its raw material and low emission of polluting gases. The objective of this research was to obtain biodiesel from the soybean oil transesterification process. The method used served as the basis for its characterization to determine if the parameters were within the range established by international legislation regarding the production of biodiesel ASTMD6751 and EN14214. Three times were used in 30, 45 and 60 minutes, the last one being the one that provided the best results with respect to the following parameters: a density of 875 kg/m3, viscosity of 3.18 mm2 /s, humidity percentage 0.029 % and an acidity index of 0.26 mgKOH/g, reaching the highest yield in this time of 69.01%. In conclusion, it can establish that both the oil and biodiesel obtained comply with international standards and above all that it could be used to obtain biofuels using vegetable oils, which opens the possibility of using it in mechanical internal combustion equipment.